PENGARUH MENINGKATNYA ARUS TRANSPORTASI SAMBAS - KUCHING MELALUI POS LINTAS BATAS NEGARA (PLBN) TERHADAP PENDAPATAN DAERAH KABUPATEN SAMBAS - Desi Yuniarti (Cross-border, 2020)
Transportation is beneficial for the community, in the sense of transporting raw materials and products to the community or company. A production will be useful and economical, if there are sufficient modes of transportation as the basis for economic development and community development as well as industrialization growth. The performance of Perum Damri Inter-Border Transportation (ALBN) for the Pontianak Kuching route is not good, this can be seen from the Load Factor Break Event (LFBE) value for all bus units, which is greater than the average load factor value for all bus units. where the LFBE value ranges from 0.55 to 0.71 while the average load factor is 0.52. The load factor value can be increased by improving services in three sectors, namely security/safety, orderliness and equality.